Effective antenatal care often improves the decision-making process among childbearing females for pursuing institutional childbirth in two South Asian Low- and middle-income countries: An appraisal of the 2019 MICS dataset - Pranta Das, Nandeeta Samad&, Razmin Bari, Ambigga Krishnapillai Devi, Halyna Lugova, Sayeeda Rahman, Rahnuma Ahmad, Khandaker Anika Afroz, Mainul Haque (Journal of Applied Pharmaceutical Science, 2021)
Antenatal care (ANC) is crucial for protecting the health and reducing the mortality of pregnant women and their unborn children. This study explores whether the number of ANC visits influences the place of delivery in Bangladesh and Nepal. The study analyzed the 2019 Multiple Indicator Cluster Survey datasets. The weighted sample size was 1,696 and 1,810 from Bangladesh and Nepal, respectively. The binary logistic regression model was run between the predictor and outcome variables while controlling the covariates to calculate both countries’ crude and adjusted odds ratios. The Hosmer–Lemeshow goodness-of-fit test evaluated each model. This study shows that the number of ANC visits is positively associated with institutional delivery in both countries. The practice of institutional delivery is predominant in Nepal (80.77%) compared to Bangladesh (56.7%), just as the number of ≥4 ANC visits is higher in Nepal (80.9%) compared to Bangladesh (43.6%). The coverage of ≥8 ANC visits was found to be low in both Bangladesh (6.5%) and Nepal (5.1%). The study has found that the women who had completed four ANC visits had about three times higher odds of having facility delivery than those who had completed below four ANC visits. In both countries, the frequency of institutional childbirth was low.
Keywords: Care, prenatal, labor place, home, hospital, delivery, MICS, Bangladesh, Nepal